Manufacture Bioplastic Composite made of Corn Starter and Poly Vinyl Alcohol with the Addition of Beeswax - Ramadhan, Aditya Prian; Purnavita, Sari; Rahayu, Lucia Hermawati (Universitas Negeri Semarang, 2022)
Bioplastics are environmentally friendly plastics that naturally can be easily degraded. One of the natural ingredients that can be used is corn starch. This study aims to study the effect of heating temperature and the addition of beeswax on the characteristics of bioplastics. This study used two independent variables. This study used the heating temperature of the material at 60-80 °C and the addition of beeswax up to 2% of the total weight. The amount of poly vinyl alcohol and corn starch was dissolved in water and further to the plasticizer in glycerol with heating time. The characteristics to be obtained are the properties of bioplastics that have been synthesized against water resistance, tensile strength, and elongation tests. The lowest heating temperature of 60 °C had a minor water absorption of 42.85%. At a heating temperature of 65 °C, it gives the highest tensile strength and elongation, respectively, 5.15 Mpa and 29.39%. The addition of beeswax affects water resistance, tensile strength, elongation, and biodegradation values. Water resistance will be higher with the addition of beeswax. In addition to 2 g of beeswax, bioplastics have the highest tensile strength value, and elongation was obtained, respectively, 9.55 Mpa and 31.54%.